On the non-identification of persons. A brief and reflective introduction to the anthropology of abortion, from antiquity to the present day - Rowiński, Tomasz (Protection of human life at the prenatal stage of development: Social, medical and legal aspects, 2026)
The chapter examines whether consent to abortion in Western civilization results from an intellectual error or a moral error subjected to secondary rationalization. It introduces superstition as a misconception about reality retained in circulation for its usefulness and, as a distortion of reality, a vehicle of violence; here it falsifies the concept of humanity applied to the unborn.The chapter traces European thought's emancipation from ancient superstitions about foetal life, including Christian engagement with the ambiguous Platonic and Aristotelian legacy, which both supported killing the unborn and enabled the construction of an integral ethics. It further examines the modern crisis marked by the parallel development of integral ethics and a revolt against the inviolability of life from conception.The material situates present-day utilitarian and integral ethical positions within their intellectual history.